Solid electrolyte modified material for diaphragm and preparation method of solid electrolyte modified material
The combined water in the solid electrolyte material is removed by spray drying and high-temperature baking treatment, and dispersed uniformly with polymers and additives in a low-water environment, and solid electrolyte modified materials with low moisture content are prepared, which solves the problem of high moisture content in the prior art and improves the stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202311409377.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-27
AI Technical Summary
In the preparation of solid electrolyte membranes, the prior art fails to effectively control the moisture content of solid electrolyte materials, resulting in high moisture content of the membrane and affecting the performance of lithium-ion batteries.
After sanding, spray drying and high-temperature baking are carried out to remove the bound water in the solid electrolyte material, and disperse it evenly with the polymer and additives under a low moisture environment. Finally, low-temperature vacuum drying and pulverizing to prepare solid electrolyte modified materials with a moisture content of less than or equal to 200ppm.
The particle size uniformity and thorough moisture removal of solid electrolyte materials are achieved, the moisture content of the separator is reduced, and the stability of lithium-ion batteries is improved.
Smart Images

Figure CN119905776A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery materials, and in particular to a solid electrolyte modified material for coating a diaphragm and a preparation method thereof. Background Art
[0002] The existing oil-based coating technology does not take into account the fact that solid electrolytes are more easily water-absorbent than traditional ceramic materials, and the initial powder is not treated for water removal after nano-sizing. In addition, traditional oil-based coating slurries are difficult to store (the slurry will have obvious sedimentation) and preserve (short shelf life and deterioration). They generally need to be made and coated immediately, and the preparation of the slurry is time-consuming and the additive ratios of each company are inconsistent, which to a certain extent limits the promotion and application of solid electrolyte materials.
[0003] Although the existing water-based coating slurry needs to be slurried under water conditions in the later stage, it does not take into account that during the nano-sizing process of the solid electrolyte, some of the bound water on the electrolyte material has a high binding energy and needs to be completely removed at a higher temperature. The moisture content of the diaphragm after coating with the untreated water-based solid electrolyte slurry will be high, which will affect the battery performance.
[0004] For example, Chinese patent CN109148794A (published on January 4, 2019) discloses an oily ceramic slurry for a diaphragm, a preparation method thereof, and a diaphragm. Although the oily ceramic slurry for the diaphragm is beneficial for reducing the moisture content of the diaphragm and improving the cycle performance of the lithium-ion battery, this patent only uses an oil-based solvent instead of an aqueous solvent to achieve the purpose of reducing the moisture content, and at the same time mixes polyvinylidene fluoride to improve the bonding force, but does not control the bound water of the ceramic powder itself, and has limited performance improvement on the lithium-ion battery. Summary of the invention
[0005] The purpose of the present invention is to provide a solid electrolyte modified material for coating a diaphragm and a preparation method thereof. Compared with the solid electrolyte material obtained by the conventional preparation method, the solid electrolyte modified material provided by the present invention has a more uniform particle size and a more thorough removal of bound water. This is because the present invention first sprays and then bakes the sand-milled solid electrolyte material to obtain a semi-finished powder material, thereby reducing the moisture content of the solid electrolyte material, wherein the spray drying is for granulation and preliminary drying, and the high-temperature baking is for reducing the bound water in the material. After that, the semi-finished powder material is used to prepare an oil-based coating slurry, and the oil-based coating slurry is subjected to low-temperature vacuum drying to completely remove the bound water in the material, and after crushing, a self-adhesive solid electrolyte modified material with a moisture content of less than or equal to 200ppm is obtained.
[0006] The solid electrolyte modified material of the present invention can fix the ratio according to needs, and can be directly mixed with an oil-based solvent to obtain a coating slurry with better uniformity. The coating slurry is used to prepare an oil-based coating diaphragm, thereby avoiding the problem that the preparation of the oil-based coating slurry in the existing oil-based coating technology is time-consuming and the addition ratios of each company are inconsistent, and the prepared slurry is easy to settle and difficult to preserve, which to a certain extent limits the promotion and application of solid electrolyte materials.
[0007] The solid electrolyte modified material of the present invention is used to prepare a diaphragm and assembled into a lithium ion battery, which can effectively improve the stability of the lithium ion battery.
[0008] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a solid electrolyte modified material for a diaphragm, the preparation method comprising:
[0009] Step S1, adding a solvent, a dispersant and a solid electrolyte material into a sand mill, and obtaining a first dispersion after sand milling;
[0010] Step S2, granulating the first dispersion by spray drying to obtain particles with a particle size D 50 A first powder between 100nm-10μm;
[0011] Step S3, baking the first powder at high temperature to obtain a second powder having a moisture content of less than or equal to 200 ppm;
[0012] Step S4, in a low-moisture environment, placing the second powder, the high molecular weight polymer, and the additive in a disperser, adding a non-aqueous solvent for dispersion treatment, and obtaining a second dispersion after uniform dispersion;
[0013] Step S5, subjecting the second dispersion to low-temperature vacuum drying treatment, and then placing it in a pulverizing device for pulverizing treatment to obtain a solid electrolyte modified material having a moisture content of less than or equal to 200 ppm;
[0014] The particle size D of the solid electrolyte modified material 50 Between 100nm-5μm.
[0015] Preferably, the solvent includes: one or more of deionized water, alcohol, N-methylpyrrolidone, dimethylformamide, and isopropanol;
[0016] The dispersant includes one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl phosphate, sodium hexametaphosphate, polyethylene glycol, polyvinyl pyrrolidone, polyacrylate, polymethacrylate, and maleic anhydride-styrene copolymer;
[0017] The solid electrolyte material comprises: one or more of lithium oxide, lithium sulfide, lithium hydride and lithium halide; the original particle size D of the solid electrolyte material is 50 Between 1μm-20μm;
[0018] The mass ratio of the solid electrolyte material to the dispersant is [95-99.99]: [0.01-5];
[0019] The solid content of the first dispersion is between 1% and 60%.
[0020] Preferably, the lithium oxide includes: garnet-type solid electrolyte, perovskite-type solid electrolyte, NASICON-type solid electrolyte, LISICON-type solid electrolyte.
[0021] Preferably, the main machine speed of the sand mill is 400rpm-3000rpm; the particle size D of the solid electrolyte material after sand milling in the first dispersion is 50 Between 50nm-5μm;
[0022] The inlet temperature of the spray drying is between 160°C and 230°C, the outlet temperature is between 50°C and 150°C, and the rotation speed of the spray centrifugal disk is 10000rpm-30000rmp.
[0023] Preferably, the high temperature baking temperature is between 250° C. and 500° C., and the baking time is between 4 hours and 24 hours.
[0024] Preferably, the high molecular polymer includes: one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polymethyl methacrylate;
[0025] The auxiliary agent includes: one or more of polyacrylonitrile, polyvinyl alcohol, polyvinyl pyrrolidone, polydimethylsiloxane, and polyoxyethylene ether;
[0026] The mass ratio of the second powder to the high molecular weight polymer is [80-99]:[1-20];
[0027] The mass ratio of the second powder to the auxiliary agent is [70-99]:[1-30];
[0028] The non-aqueous solvent includes one or more of alcohol, N-methylpyrrolidone, tetrahydrofuran, dimethylacetamide, isopropanol, ethyl acetate or acetone;
[0029] The solid content of the second dispersion is between 1% and 60%;
[0030] The dew point of the low moisture environment is between -10°C and -60°C;
[0031] The rotation speed of the disperser is between 1000 rpm and 3000 rpm, and the time of the dispersion treatment is between 30 minutes and 5 hours.
[0032] Preferably, the drying temperature of the low-temperature vacuum drying treatment is between 50°C and 120°C, the drying time is between 5 hours and 24 hours, and the vacuum degree is less than or equal to 150Pa;
[0033] The pulverizing equipment is a jet mill, the frequency of the jet mill is 50 Hz-100 Hz, and the pulverizing time is 1 hour-2 hours.
[0034] In a second aspect, an embodiment of the present invention provides a solid electrolyte modified material prepared by the preparation method described in the first aspect, wherein the solid electrolyte modified material comprises: 80wt%-97wt% of a solid electrolyte material, 1wt%-5wt% of a dispersant, 1wt%-20wt% of a high molecular polymer, and 1wt%-30wt% of an additive;
[0035] The solid electrolyte material includes: one or more of lithium oxide, lithium sulfide, lithium hydride and lithium halide; wherein the lithium oxide includes: garnet-type solid electrolyte, perovskite-type solid electrolyte, NASICON-type solid electrolyte and LISICON-type solid electrolyte;
[0036] The high molecular polymer includes: one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polymethyl methacrylate;
[0037] The auxiliary agent includes: one or more of polyacrylonitrile, polyvinyl alcohol, polyvinyl pyrrolidone, polydimethylsiloxane, and polyoxyethylene ether;
[0038] The particle size D of the solid electrolyte modified material 50 Between 100nm-5μm; the moisture content of the solid electrolyte modified material is less than or equal to 200ppm.
[0039] In a third aspect, an embodiment of the present invention provides a diaphragm, wherein the diaphragm includes the solid electrolyte modified material described in the second aspect.
[0040] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the separator described in the third aspect.
[0041] The embodiment of the present invention provides a preparation method of a solid electrolyte modified material for a diaphragm, firstly grinding the solid electrolyte material to a specified particle size by wet sand milling, granulating by spray drying at a certain temperature, and then removing all bound water in the material by high-temperature baking, and in a low-moisture environment, the solid electrolyte material and the high molecular polymer without bound water are evenly dispersed in a non-aqueous solvent in a certain proportion, and then subjected to low-temperature vacuum drying and pulverization to obtain a solid electrolyte modified material with a water content of less than or equal to 200 ppm; the preparation method provided by the embodiment of the present invention is simple to operate, can be applied to large-scale production, and has practical significance for industrial applications.
[0042] Compared with the solid electrolyte material obtained by the conventional preparation method, the solid electrolyte modified material provided by the present invention has a more uniform particle size and more thorough removal of bound water. This is because the present invention first sprays and then bakes the sand-milled solid electrolyte material to obtain a semi-finished powder material, thereby reducing the moisture content of the solid electrolyte material, wherein the spray drying is for granulation and preliminary drying, and the high-temperature baking is for reducing the bound water in the solid electrolyte material. After that, the semi-finished powder material is used to prepare an oil-based coating slurry, and the oil-based coating slurry is subjected to low-temperature vacuum drying to completely remove the bound water in the material, and after pulverization, a self-adhesive solid electrolyte modified material with a moisture content of less than or equal to 200 ppm is obtained.
[0043] The solid electrolyte modified material of the present invention can fix the ratio according to needs, and can be directly mixed with an oil-based solvent to obtain a slurry for the preparation of an oil-based coating diaphragm, thereby avoiding the problem that the preparation of the oil-based coating slurry in the existing oil-based coating technology is time-consuming and the addition ratios of each manufacturer are inconsistent, and the prepared slurry is easy to settle and difficult to preserve, which to a certain extent limits the promotion and application of solid electrolyte materials.
[0044] The solid electrolyte modified material of the present invention is used to prepare a diaphragm and assembled into a lithium ion battery, which can effectively improve the stability of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0046] Figure 1 It is a flow chart of a method for preparing a solid electrolyte modified material provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0048] The present invention provides a method for preparing a solid electrolyte modified material for a diaphragm. Figure 1 As shown, the preparation method comprises the following steps:
[0049] Step S1, adding a solvent, a dispersant and a solid electrolyte material into a sand mill, and obtaining a first dispersion after sand milling;
[0050] The solvent includes one or more of deionized water, alcohol, N-methylpyrrolidone, dimethylformamide, and isopropanol;
[0051] The dispersant includes one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl phosphate, sodium hexametaphosphate, polyethylene glycol, polyvinyl pyrrolidone, polyacrylate, polymethacrylate, and maleic anhydride-styrene copolymer;
[0052] The solid electrolyte material includes one or more of lithium oxide, lithium sulfide, lithium hydride and lithium halide; the original particle size D of the solid electrolyte material is 50 Between 1μm-20μm; lithium oxides include: garnet-type solid electrolyte, perovskite-type solid electrolyte, NASICON-type solid electrolyte, LISICON-type solid electrolyte;
[0053] The mass ratio of the solid electrolyte material to the dispersant is [95-99.99]:[0.01-5];
[0054] The solid content of the first dispersion is between 1% and 60%;
[0055] The main machine speed of the sand mill is 400rpm-3000rpm; the particle size D of the solid electrolyte material after sand milling in the first dispersion 50 Between 50nm-5μm.
[0056] Step S2, granulating the first dispersion by spray drying to obtain particles with a particle size D 50 A first powder between 100nm-10μm;
[0057] The inlet temperature of the spray drying is between 160°C and 230°C, the outlet temperature is between 50°C and 150°C, and the rotation speed of the spray centrifugal disk is 10000rpm-30000rmp.
[0058] Step S3, baking the first powder at high temperature to obtain a second powder having a moisture content of less than or equal to 200 ppm;
[0059] The high temperature baking temperature is between 250°C and 500°C, and the baking time is between 4 hours and 24 hours;
[0060] The moisture content of the second powder obtained in this step is less than or equal to 200 ppm. By preparing a slurry using the second powder obtained in this step for use in a water-based coated diaphragm, the moisture content of the water-based coated diaphragm can be effectively reduced, verifying that the performance of the second powder is superior to that of ordinary solid electrolyte materials. Pre-preparing a second powder with a moisture content of less than or equal to 200 ppm is beneficial to the subsequent step of preparing a solid electrolyte modified material with a low moisture content.
[0061] Step S4, in a low-moisture environment, placing the second powder, the high molecular weight polymer, and the additive in a disperser, adding a non-aqueous solvent for dispersion treatment, and obtaining a second dispersion after uniform dispersion;
[0062] Wherein, the high molecular polymer includes: one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethyl methacrylate (PMMA);
[0063] The auxiliary agent includes: one or more of polyacrylonitrile, polyvinyl alcohol, polyvinyl pyrrolidone, polydimethylsiloxane, and polyoxyethylene ether;
[0064] The mass ratio of the second powder to the high molecular weight polymer is [80-99]:[1-20];
[0065] The mass ratio of the second powder to the additive is [70-99]:[1-30];
[0066] The non-aqueous solvent includes one or more of alcohol, N-methylpyrrolidone, tetrahydrofuran, dimethylacetamide, isopropanol, ethyl acetate or acetone;
[0067] The solid content of the second dispersion is between 1% and 60%;
[0068] The dew point of a low-moisture environment is between -10°C and -60°C;
[0069] The speed of the disperser is between 1000 rpm and 3000 rpm, and the dispersion treatment time is between 30 minutes and 5 hours.
[0070] Step S5, subjecting the second dispersion to low-temperature vacuum drying treatment, and then placing it in a pulverizing device for pulverizing treatment to obtain a solid electrolyte modified material having a moisture content of less than or equal to 200 ppm;
[0071] The drying temperature of the low-temperature vacuum drying treatment is between 50°C and 120°C, the drying time is between 5 hours and 24 hours, and the vacuum degree is less than or equal to 150Pa;
[0072] The crushing equipment is a jet mill, the frequency of the jet mill is 50Hz-100Hz, and the crushing time is 1 hour-2 hours;
[0073] Particle size D of the prepared solid electrolyte modified material 50 Between 100nm-5μm, preferably 300nm-800nm.
[0074] Traditionally, in the process of preparing the diaphragm coating slurry, a sand grinding nano-process as in step S1 of the preparation method of the present invention is used. During the sand grinding process, the solid electrolyte material forms a high-energy hydrate with water. If the high-energy hydrate is directly mixed with a conductive agent, a binder, an auxiliary agent, etc. to prepare a coating slurry and then coated to prepare a diaphragm, the moisture content of the diaphragm will be high, and even if the diaphragm is baked, the bound water in the solid electrolyte material cannot be removed, which will affect the stability of the lithium-ion battery.
[0075] The solid electrolyte modified material prepared by the above preparation method in the embodiment of the present invention comprises 80wt%-97wt% of solid electrolyte material, 1wt%-5wt% of dispersant, 1wt%-20wt% of high molecular polymer and 1wt%-30wt% of auxiliary agent.
[0076] Among them, the solid electrolyte material includes: one or more of lithium oxide, lithium sulfide, lithium hydride and lithium halide; among them, the lithium oxide includes: garnet-type solid electrolyte, perovskite-type solid electrolyte, NASICON-type solid electrolyte and LISICON-type solid electrolyte.
[0077] The high molecular polymer includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polymethyl methacrylate.
[0078] The auxiliary agent includes: one or more of polyacrylonitrile, polyvinyl alcohol, polyvinyl pyrrolidone, polydimethylsiloxane and polyoxyethylene ether.
[0079] Particle size D of solid electrolyte modified material 50 The particle size is between 100 nm and 5 μm, preferably between 300 nm and 800 nm; the water content of the solid electrolyte modified material is less than or equal to 200 ppm.
[0080] The above-mentioned solid electrolyte modified material can be directly mixed with an oily solvent or an aqueous solvent to prepare a slurry for coating a diaphragm. Since the solid electrolyte modified material does not need to be sanded and nano-sized during the slurry preparation process, the solid electrolyte material in the solid electrolyte modified material will not form hydrates with water, and the solid electrolyte modified material itself has a low water content, so the prepared diaphragm has a low water content. The diaphragm containing the solid electrolyte modified material of the present invention is assembled into a lithium ion battery, which can improve the stability of the lithium ion battery.
[0081] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the solid electrolyte modified material of the present invention are respectively described below with multiple specific examples.
[0082] Example 1
[0083] This embodiment provides a preparation process and performance test of a solid electrolyte modified material, and the specific process is as follows:
[0084] (1) Add 2 kg of deionized water, 5 g of dispersant polymethacrylate and 0.5 kg of solid electrolyte material Li with a particle size of 4 μm into a sand mill. 1.3 Al 0.3 Ti 1.7 (PO4), the rotation speed of the sand mill is set to 2200 rpm, and a first dispersion is obtained after sand milling for 2 hours. The average particle size of the solid material in the first dispersion is 400 nm.
[0085] (2) The first dispersion is granulated by spray drying. The parameters of the spray dryer are set as follows: the inlet temperature is 180°C, the outlet temperature is 130°C, the spray centrifugal disk speed is 15000 rpm, and the particle size D is obtained after spray drying. 50 The first powder is 450 nm.
[0086] (3) The first powder is baked at high temperature in an oven at 380° C. for 8 hours to obtain a second powder with a moisture content of 90 ppm.
[0087] (4) Under a dew point environment of -40°C, 0.5 kg of the second powder, 80 g of PVDF-HFP, and 5 g of polyvinyl pyrrolidone were placed in a disperser, and 2 kg of N-methylpyrrolidone (NMP) was added for dispersion treatment. The mixture was dispersed at a speed of 2000 r / min for 4 hours, and the second dispersion was obtained after uniform dispersion.
[0088] (5) The second dispersion was subjected to low-temperature vacuum drying treatment, the temperature of the low-temperature vacuum drying treatment was set to 80° C., the drying time was 10 hours, the vacuum degree was 130 Pa, and after drying, it was placed in a pulverizing device for pulverization treatment, the frequency of the pulverizer was 80 Hz, and a solid electrolyte modified material with a moisture content of 110 ppm and a particle size D 50 is 500nm.
[0089] The second powder of the intermediate product step (3) prepared in this embodiment is used to prepare a water-based coated diaphragm, specifically: 0.5 kg of the second powder obtained in the above step (3), 2 kg of deionized water, 3 g of sodium carboxymethyl cellulose (CMC), 60 g of styrene-butadiene rubber (SBR), 3 g of polyethylene glycol, and 10 g of polyether-modified siloxane are dispersed in a disperser for 4 hours, and the disperser speed is 2000 rpm. The obtained water-based coating slurry is coated on 9 μm polyethylene (PE), with a coating thickness of 2 μm and a coating drying temperature of 65°C to obtain a water-based coated diaphragm. The moisture content of the water-based coated diaphragm prepared in this embodiment is tested at 150°C, 180°C, and 200°C, respectively, and the dew point of the test environment is -40°C. The test data are shown in Table 1.
[0090] The solid electrolyte modified material prepared in this embodiment is used to prepare an oil-based coated diaphragm, specifically: 0.5 kg of the crushed solid electrolyte modified material and 2 kg of NMP are dispersed in a disperser for 0.5 hours to obtain an oil-based coated slurry, which is coated on a 9 μm PE base film with a coating thickness of 1 μm and a coating drying temperature of 80°C to obtain an oil-based coated diaphragm. The moisture content of the oil-based coated diaphragm prepared in this embodiment is tested at 150°C, 180°C, and 200°C, respectively, and the dew point of the test environment is -40°C. The moisture content and membrane surface flatness test data are shown in Table 2.
[0091] The oil-based coated diaphragm prepared in this example is used to prepare a lithium-ion battery, and the specific process is as follows:
[0092] Preparation of positive electrode sheet: active material lithium cobalt oxide, conductive carbon black, binder polyvinylidene fluoride, solvent NMP are stirred and mixed in a mass ratio of 64:3:3:30, coated on aluminum foil, dried, cold pressed, and slit to prepare positive electrode sheet;
[0093] Preparation of negative electrode sheet: active material graphite, binder styrene-butadiene rubber, thickener sodium carboxymethyl cellulose, and deionized water are stirred and mixed in a mass ratio of 62:2:1:35, coated on copper foil, dried, cold pressed, and cut into strips to prepare negative electrode sheet;
[0094] The positive electrode plate, the oil-based coated diaphragm prepared in this embodiment (wherein the side containing the solid electrolyte modification material faces the negative electrode), and the negative electrode plate are stacked in order and wound to obtain a bare battery cell, the bare battery cell is placed in a shell, and an electrolyte is injected and packaged to obtain a lithium-ion battery; wherein the electrolyte is a 1 mol / L LiPF6 ethylene carbonate EC / dimethyl carbonate DEC (the volume ratio of EC to DEC is 1:1) solution.
[0095] The test cycle process is: at 25°C, charge to 4.4V at a constant current rate of 1C, then charge to 0.05C at a constant voltage of 4.4V, and then discharge to 2.0V at a discharge current of 1C, and then repeat the above process to test the coulomb efficiency of the first week and the cycle capacity retention rate after 500 cycles. The test data are detailed in Table 3.
[0096] Example 2
[0097] This embodiment provides a preparation process and performance test of a solid electrolyte modified material, and the specific process is as follows:
[0098] (1) Add 2 kg of alcohol, 3 g of dispersant polyvinyl pyrrolidone and 0.5 kg of solid electrolyte material Li with a particle size of 5 μm into a sand mill. 0.33 La 0.57 TiO3, the speed of the sand mill is set to 2000 rpm, and the first dispersion is obtained after sand milling for 3 hours. The average particle size of the solid material in the first dispersion is 350 nm.
[0099] (2) The first dispersion is granulated by spray drying. The parameters of the spray dryer are set as follows: the inlet temperature is 150°C, the outlet temperature is 125°C, the spray centrifugal disk speed is 16000 rpm, and the particle size D is obtained after spray drying. 50 The first powder is 400 nm.
[0100] (3) The first powder was baked in an oven at 350° C. for 10 hours to obtain a second powder having a moisture content of 100 ppm.
[0101] (4) Under a dew point environment of -40°C, 0.5 kg of the second powder, 80 g of PVDF-HFP, and 5 g of polyvinyl alcohol were placed in a disperser, 2 kg of dimethylacetamide was added for dispersion treatment, and the mixture was dispersed at a speed of 2200 rpm for 4 hours. After uniform dispersion, a second dispersion was obtained.
[0102] (5) The second dispersion is subjected to low-temperature vacuum drying treatment, the temperature of the low-temperature vacuum drying treatment is set to 85° C., the drying time is 8 hours, the vacuum degree is 135 Pa, and after drying, it is placed in a pulverizing device for pulverization treatment, the frequency of the pulverizer is 75 Hz, and a solid electrolyte modified material with a moisture content of 100 ppm and a particle size D 50 is 500nm.
[0103] The second powder of the intermediate product step (3) prepared in this embodiment is used to prepare a water-based coated diaphragm. The specific process is the same as that in Example 1. The moisture content of the water-based coated diaphragm prepared in this embodiment is tested at 150°C, 180°C, and 200°C, respectively. The dew point of the test environment is -40°C. The test data is shown in Table 1.
[0104] The solid electrolyte modified material prepared in this embodiment is used to prepare an oil-based coated diaphragm. The specific process is the same as that in Example 1. The moisture content of the oil-based coated diaphragm prepared in this embodiment is tested at 150°C, 180°C, and 200°C, respectively. The dew point of the test environment is -40°C. The moisture content and membrane surface flatness test data are shown in Table 2.
[0105] The oil-based coated diaphragm prepared in this example was used to prepare a lithium-ion battery and tested. The specific process was the same as that in Example 1. The test data is shown in Table 3.
[0106] To better illustrate the effects of the embodiments of the present invention, Comparative Examples 1-2 are compared with the water-based coated membranes prepared in Embodiment 1-2, and Comparative Examples 3-6 are compared with the oil-based coated membranes prepared in Embodiment 1-2.
[0107] Comparative Example 1
[0108] In this comparative example, the first dispersion liquid with an average particle size of 400 nm of the solid material prepared in step (1) of Example 1 is directly used to prepare the water-based coated diaphragm. The specific preparation process is: 2.5 kg of the first dispersion liquid, 3 g of CMC, 60 g of SBR, 3 g of polyethylene glycol, and 10 g of polyether-modified siloxane are placed in a disperser and dispersed for 4 hours at a disperser speed of 2000 rpm. The obtained water-based coating slurry is coated on a PE base film at 9 μm with a coating thickness of 2 μm and a coating drying temperature of 65°C to obtain a water-based coated diaphragm.
[0109] The moisture content of the water-based coated diaphragm prepared in this comparative example was tested at 150° C., 180° C., and 200° C., respectively. The dew point of the test environment was -40° C. The test data are shown in Table 1.
[0110] The oil-based coated diaphragm prepared in this comparative example was used to assemble a lithium-ion battery. The specific assembly process and test process were the same as those in Example 1. The test data are shown in Table 3.
[0111] Comparative Example 2
[0112] In this comparative example, the first dispersion liquid with an average particle size of 350 nm of the solid material prepared in step (1) of Example 2 is directly used to prepare the water-based coated diaphragm. The specific preparation process is: 2.5 kg of the first dispersion liquid, 3 g of CMC, 60 g of SBR, 3 g of polyethylene glycol, and 10 g of polyether-modified siloxane are placed in a disperser and dispersed for 4 hours at a disperser speed of 2000 rpm. The obtained water-based coating slurry is coated on a PE base film at 9 μm with a coating thickness of 2 μm and a coating drying temperature of 65°C to obtain a water-based coated diaphragm.
[0113] The moisture content of the water-based coated diaphragm prepared in this comparative example was tested at 150° C., 180° C., and 200° C., respectively. The dew point of the test environment was -40° C. The test data are shown in Table 1.
[0114] The oil-based coated diaphragm prepared in this comparative example was used to assemble a lithium-ion battery. The specific assembly process and test process were the same as those in Example 1. The test data are shown in Table 3.
[0115] Comparative Example 3
[0116] This comparative example provides a solid electrolyte dispersion and prepares an oil-based coated diaphragm. The difference from Example 1 is that the preparation process of the solid electrolyte dispersion of the present invention does not include step (2) of spray granulation at a certain temperature, step (3) of high temperature baking, and step (4) of low temperature vacuum drying in Example 1. The specific preparation process of the solid electrolyte dispersion is as follows:
[0117] In an environment with a dew point of -40°C, the solid electrolyte material Li with a particle size of 4 μm was 1.3 Al 0.3 Ti 1.7 (PO4) was dried in an oven at 150°C for 8 hours to obtain a powder with a moisture content of 350 ppm; the powder was added to a sand mill together with 5 g of polyvinyl pyrrolidone and 2 kg of N-methyl pyrrolidone, and the speed of the sand mill was set to 2200 rpm. The sand mill was treated for 2 hours to obtain a first dispersion, and the average particle size of the solid material in the first dispersion was 450 nm; the first dispersion was added to a disperser together with 80 g of PVDF-HFP in a dry room environment at -40°C, and dispersed at a speed of 2000 rpm for 2 hours to obtain a solid electrolyte dispersion.
[0118] The solid electrolyte dispersion prepared in this comparative example was used to prepare an oil-based coated diaphragm, specifically: 2.5 kg of the solid electrolyte dispersion was coated on a 9 μm PE base film, with a coating thickness of 1 μm and a coating drying temperature of 80°C to obtain an oil-based coated diaphragm. The moisture content of the oil-based coated diaphragm prepared in this comparative example was tested at 150°C, 180°C, and 200°C, respectively, with a test environment dew point of -40°C. The moisture content and membrane surface flatness test data are shown in Table 2.
[0119] The oil-based coated diaphragm prepared in this comparative example was used to assemble a lithium-ion battery. The specific assembly process and test process were the same as those in Example 1. The test data are shown in Table 3.
[0120] Comparative Example 4
[0121] This comparative example provides a solid electrolyte dispersion and prepares an oil-based coated diaphragm. The difference from Example 1 is that the preparation process of the solid electrolyte dispersion of the present invention does not include step (2) of spray granulation at a certain temperature, step (3) of high temperature baking, and step (4) of low temperature vacuum drying in Example 1. The specific preparation process of the solid electrolyte dispersion is as follows:
[0122] In an environment with a dew point of -40°C, the solid electrolyte material Li with a particle size of 4 μm was 1.3 Al 0.3 Ti 1.7 (PO4) was dried in an oven at 150°C for 8 hours to obtain a powder with a moisture content of 350 ppm; the powder was added to a sand mill together with 5 g of polyvinyl pyrrolidone and 2 kg of N-methyl pyrrolidone, and the speed of the sand mill was set to 2200 rpm. The sand mill was treated for 2 hours to obtain a first dispersion, and the average particle size of the solid material in the first dispersion was 450 nm; the first dispersion was added to a disperser together with 80 g of PVDF-HFP in a dry room environment at -40°C, and dispersed at a speed of 2000 rpm for 4 hours to obtain a solid electrolyte dispersion.
[0123] The solid electrolyte dispersion prepared in this comparative example was used to prepare an oil-based coated diaphragm, specifically: 2.5 kg of the solid electrolyte dispersion was coated on a 9 μm PE base film, with a coating thickness of 1 μm and a coating drying temperature of 80°C to obtain an oil-based coated diaphragm. The moisture content of the oil-based coated diaphragm prepared in this comparative example was tested at 150°C, 180°C, and 200°C, respectively, with a test environment dew point of -40°C. The moisture content and membrane surface flatness test data are shown in Table 2.
[0124] The oil-based coated diaphragm prepared in this comparative example was used to assemble a lithium-ion battery. The specific assembly process and test process were the same as those in Example 1. The test data are shown in Table 3.
[0125] Comparative Example 5
[0126] This comparative example provides a solid electrolyte dispersion and prepares an oil-based coated diaphragm. The difference from Example 2 is that the preparation process of the solid electrolyte dispersion of the present invention does not include step (2) of spray granulation at a certain temperature, step (3) of high temperature baking, and step (4) of low temperature vacuum drying in Example 2. The specific preparation process of the solid electrolyte dispersion is as follows:
[0127] In an environment with a dew point of -40°C, the solid electrolyte material Li with a particle size of 5 μm was 0.33 La 0.57 TiO3 was dried in an oven at 150°C for 8 hours to obtain a powder with a moisture content of 330 ppm; the powder was added to a sand mill together with 5 g of polyvinyl alcohol and 2 kg of N-methylpyrrolidone for sand grinding, and the speed of the sand mill was set to 2000 rpm. The sand grinding was performed for 3 hours to obtain a first dispersion, and the average particle size of the solid material in the first dispersion was 350 nm; the first dispersion was added to a disperser together with 80 g of PVDF-HFP in a dry room environment at -40°C, and dispersed at a speed of 2200 rpm for 2 hours to obtain a solid electrolyte dispersion.
[0128] The solid electrolyte dispersion prepared in this comparative example was used to prepare an oil-based coated diaphragm, specifically: 2.5 kg of the solid electrolyte dispersion was coated on a 9 μm PE base film, with a coating thickness of 1 μm and a coating drying temperature of 80°C to obtain an oil-based coated diaphragm. The moisture content of the oil-based coated diaphragm prepared in this comparative example was tested at 150°C, 180°C, and 200°C, respectively, with a test environment dew point of -40°C. The moisture content and membrane surface flatness test data are shown in Table 2.
[0129] The oil-based coated diaphragm prepared in this comparative example was used to assemble a lithium-ion battery. The specific assembly process and test process were the same as those in Example 1. The test data are shown in Table 3.
[0130] Comparative Example 6
[0131] This comparative example provides a solid electrolyte dispersion and prepares an oil-based coated diaphragm. The difference from Example 2 is that the preparation process of the solid electrolyte dispersion of the present invention does not include step (2) of spray granulation at a certain temperature, step (3) of high temperature baking, and step (4) of low temperature vacuum drying in Example 2. The specific preparation process of the solid electrolyte dispersion is as follows:
[0132] In an environment with a dew point of -40°C, the solid electrolyte material Li with a particle size of 5 μm was 0.33 La 0.57TiO3 was dried in an oven at 150°C for 8 hours to obtain a powder with a moisture content of 330 ppm; the powder was added to a sand mill together with 5 g of polyvinyl alcohol and 2 kg of N-methylpyrrolidone for sand grinding, and the speed of the sand mill was set to 2000 rpm. The sand grinding was performed for 3 hours to obtain a first dispersion, and the average particle size of the solid material in the first dispersion was 350 nm; the first dispersion was added to a disperser together with 80 g of PVDF-HFP in a dry room environment at -40°C, and dispersed at a speed of 2200 rpm for 4 hours to obtain a solid electrolyte dispersion.
[0133] The solid electrolyte dispersion prepared in this comparative example was used to prepare an oil-based coated diaphragm, specifically: 2.5 kg of the solid electrolyte dispersion was coated on a 9 μm PE base film, with a coating thickness of 1 μm and a coating drying temperature of 80°C to obtain an oil-based coated diaphragm. The moisture content of the oil-based coated diaphragm prepared in this comparative example was tested at 150°C, 180°C, and 200°C, respectively, with a test environment dew point of -40°C. The moisture content and membrane surface flatness test data are shown in Table 2.
[0134] The oil-based coated diaphragm prepared in this comparative example was used to assemble a lithium-ion battery. The specific assembly process and test process were the same as those in Example 1. The test data are shown in Table 3.
[0135] Table 1 is a summary of the test data of the moisture content of the water-based coated diaphragms prepared in Examples 1-2 and Comparative Examples 1-2:
[0136]
[0137] Table 1
[0138] It can be seen from the test data in Table 1 that the moisture content of the water-based coated membranes of Examples 1-2 was less than 1000ppm when tested at 150°C, while the moisture content of Comparative Examples 1-2 was above 1500ppm. At the same time, with the increase of the test temperature, the moisture content of the membranes of Comparative Examples 1-2 increased significantly, while the moisture content of the samples of the embodiments changed little with the test temperature, indicating that the bound water in Examples 1-2 has been discharged, and high-energy bound water will not be introduced into the material in the conventional water-based dispersion process, verifying the performance of the powder obtained by spray drying and high-temperature baking twice in the preparation process of the present invention. Due to the ordinary solid electrolyte material that has not been baked twice, the two processes of spray drying and high-temperature baking in the preparation process of the present invention have advantages, and the obtained second powder can be directly used as a solid electrolyte material for the preparation of water-based coated membranes. At the same time, it is beneficial to prepare solid electrolyte modified materials with low moisture content in subsequent steps.
[0139] Table 2 is a summary of the moisture content and flatness test results of the oil-based coated diaphragms prepared in Examples 1-2 and Comparative Examples 3-6 at different temperatures:
[0140]
[0141] Table 2
[0142] From the test data in Table 2, it can be seen that the oil-based coated diaphragms prepared in Examples 1-2 have low moisture content when rolled up at 150°C. However, as the test temperature increases, the moisture content of the diaphragms of Comparative Examples 3-4 increases significantly, indicating that part of the bound water in the solid electrolyte material can only be baked out at high temperatures, verifying that the secondary baking method of the present invention has obvious advantages.
[0143] During the on-site pulping process, the slurry of Examples 1-2 only needs to be dispersed for 0.5 hours, while the membrane surface of the slurry of Comparative Examples 3 and 5 after being dispersed for 2 hours is uneven, with scratches and missing spots. The membrane surface of Comparative Examples 3 and 5 after being dispersed for 4 hours is flawless, which is equivalent to that of Examples 1-2 after being dispersed for 0.5 hours, indicating that the solid electrolyte modified material prepared by the embodiments of the present invention can greatly improve the production efficiency.
[0144] Table 3 is a summary of the test data of lithium-ion batteries assembled with oil-based coated diaphragms prepared in Examples 1-2 and Comparative Examples 3-6:
[0145]
[0146]
[0147] Table 3
[0148] From the test data in Table 3, it can be seen that the first-week coulombic efficiency and the cycle capacity retention rate after 500 cycles of the lithium-ion batteries assembled with the diaphragms containing solid electrolyte modified materials in Examples 1-2 of the present invention are better than those of the lithium-ion batteries assembled in Comparative Examples 3-6, indicating that the solid electrolyte modified materials provided in the embodiments of the present invention can improve the stability of lithium-ion batteries.
[0149] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a solid electrolyte modified material for a diaphragm, characterized in that: The preparation method comprises: Step S1, adding a solvent, a dispersant and a solid electrolyte material into a sand mill, and obtaining a first dispersion after sand milling; Step S2, granulating the first dispersion by spray drying to obtain particles with a particle size D 50 A first powder between 100nm-10μm; Step S3, baking the first powder at high temperature to obtain a second powder having a moisture content of less than or equal to 200 ppm; Step S4, in a low-moisture environment, placing the second powder, the high molecular weight polymer, and the additive in a disperser, adding a non-aqueous solvent for dispersion treatment, and obtaining a second dispersion after uniform dispersion; Step S5, subjecting the second dispersion to low-temperature vacuum drying treatment, and then placing it in a pulverizing device for pulverizing treatment to obtain a solid electrolyte modified material having a moisture content of less than or equal to 200 ppm; The particle size D of the solid electrolyte modified material 50 Between 100nm-5μm.
2. The preparation method according to claim 1, characterized in that: The solvent includes: one or more of deionized water, alcohol, N-methylpyrrolidone, dimethylformamide, and isopropanol; The dispersant includes one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl phosphate, sodium hexametaphosphate, polyethylene glycol, polyvinyl pyrrolidone, polyacrylate, polymethacrylate, and maleic anhydride-styrene copolymer; The solid electrolyte material comprises: one or more of lithium oxide, lithium sulfide, lithium hydride and lithium halide; the original particle size D of the solid electrolyte material is 50 Between 1μm-20μm; The mass ratio of the solid electrolyte material to the dispersant is [95-99.99]: [0.01-5]; The solid content of the first dispersion is between 1% and 60%.
3. The preparation method according to claim 2, characterized in that: The lithium oxides include: garnet-type solid electrolytes, perovskite-type solid electrolytes, NAS ICON-type solid electrolytes, and LISICON-type solid electrolytes.
4. The preparation method according to claim 1, characterized in that: The main machine speed of the sand mill is 400rpm-3000rpm; the particle size D of the solid electrolyte material after sand milling in the first dispersion is 50 Between 50nm-5μm; The inlet temperature of the spray drying is between 160°C and 230°C, the outlet temperature is between 50°C and 150°C, and the rotation speed of the spray centrifugal disk is 10000rpm-30000rmp.
5. The preparation method according to claim 1, characterized in that: The high temperature baking temperature is between 250° C. and 500° C., and the baking time is between 4 hours and 24 hours.
6. The preparation method according to claim 1, characterized in that: The high molecular polymer includes: one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polymethyl methacrylate; The auxiliary agent includes: one or more of polyacrylonitrile, polyvinyl alcohol, polyvinyl pyrrolidone, polydimethylsiloxane, and polyoxyethylene ether; The mass ratio of the second powder to the high molecular weight polymer is [80-99]:[1-20]; The mass ratio of the second powder to the auxiliary agent is [70-99]:[1-30]; The non-aqueous solvent includes one or more of alcohol, N-methylpyrrolidone, tetrahydrofuran, dimethylacetamide, isopropanol, ethyl acetate or acetone; The solid content of the second dispersion is between 1% and 60%; The dew point of the low moisture environment is between -10°C and -60°C; The rotation speed of the disperser is between 1000 rpm and 3000 rpm, and the time of the dispersion treatment is between 30 minutes and 5 hours.
7. The preparation method according to claim 1, characterized in that: The low-temperature vacuum drying process has a drying temperature between 50°C and 120°C, a drying time between 5 hours and 24 hours, and a vacuum degree less than or equal to 150Pa; The pulverizing equipment is a jet mill, the frequency of the jet mill is 50 Hz-100 Hz, and the pulverizing time is 1 hour-2 hours.
8. A solid electrolyte modified material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The solid electrolyte modified material comprises: 80wt%-97wt% of solid electrolyte material, 1wt%-5wt% of dispersant, 1wt%-20wt% of high molecular polymer and 1wt%-30wt% of auxiliary agent; The solid electrolyte material includes: one or more of lithium oxide, lithium sulfide, lithium hydride and lithium halide; wherein the lithium oxide includes: garnet-type solid electrolyte, perovskite-type solid electrolyte, NASICON-type solid electrolyte and LIS ICON-type solid electrolyte; The high molecular polymer includes: one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polymethyl methacrylate; The auxiliary agent includes: one or more of polyacrylonitrile, polyvinyl alcohol, polyvinyl pyrrolidone, polydimethylsiloxane, and polyoxyethylene ether; The particle size D of the solid electrolyte modified material 50 Between 100nm-5μm; the moisture content of the solid electrolyte modified material is less than or equal to 200ppm.
9. A diaphragm, characterized in that: The separator comprises the solid electrolyte modifying material as claimed in claim 8 above.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the separator according to claim 9.
Citation Information
Patent Citations
Water-based solid electrolyte membrane, preparation method thereof, and secondary battery
CN108598563A
Low-moisture lithium ion battery ceramic-coated diaphragm and preparation method thereof
CN109461866A
Preparation method of high-density and high-ionic conductivity electrolyte diaphragm for all-solid-state battery
CN111900310A
Nanometer solid electrolyte slurry and preparation method and application thereof
CN115579513A